Alopecia neoplastica as a sign of visceral malignancies: a systematic review. (12th March 2019) - Paolino, G.; Pampena, R.; Grassi, S.; Mercuri, S.R.; Cardone, M.; Corsetti, P.; Moliterni, E.; Muscianese, M.; Rossi, A.; Frascione, P.; Longo, C.
Abstract: Alopecia neoplastica (AN) from visceral tumours is a rare form of cutaneous metastasis in which internal malignancies spread to the scalp. The diagnosis of AN may be very challenging, especially when its onset precedes the diagnosis of the primary tumour. We aimed to improve the knowledge on AN, highlighting that in case of scarring localized alopecia, a differential diagnosis with metastasis should always be considered. We performed a systematic review to describe the main demographic and clinical features associated with AN from visceral malignancies; a survival analysis was also performed. In 118 reports, accounting for 123 patients, we found that women were more affected by AN than men (53.7% vs. 46.3%). The most frequent site of the primary tumour was the gastrointestinal tract (24.4%), followed by breast (17.9%), kidney (8.1%), lung (7.3%), thyroid (7.3%), uterus (6.5%), central nervous system (6.5%), liver (3.3%) and other anatomic areas for 18.7% of cases. Furthermore, in more than half of the cases (66.1%), AN lesions were single and were mainly diagnosed after the primary visceral tumour (71.5%). Finally, survival analysis highlighted a lower progression‐free survival in men; while, no significant differences in overall survival were reported among genders. In conclusion, metastatic skin disease should always be taken into consideration when dealing with patients with localized scarring alopecia.